ChatGPT in Social Studies Education: A Systematic Literature Review of Critical Thinking and Collaborative Learning in Junior High Schools (2023–2026) - Isnaeni Fatmiyati; Bambang Syaeful Hadi (Penerbit Hellow Pustaka, 2026)
This study aims to synthesize and analyze the development of research on the use of ChatGPT in Social Studies education to support the development of critical thinking and collaborative learning skills among junior high school students during the 2023–2026 period. This study employed a Systematic Literature Review approach following the PRISMA 2020 guidelines. Literature searches were conducted across Scopus, ERIC, Dimensions, and Google Scholar using keywords related to ChatGPT, Social Studies education, critical thinking, collaborative learning, and junior high school contexts. The inclusion criteria comprised peer-reviewed journal articles published between 2023 and 2026, written in English or Indonesian, focused on Social Studies education, and available in full text. The selection process resulted in eight eligible articles for analysis. The findings indicate that publications on the use of ChatGPT in education have increased substantially since 2023; however, studies specifically addressing Social Studies education at the junior high school level remain limited. The thematic analysis identified four major benefits of ChatGPT, including enhanced critical thinking skills, support for personalized learning, strengthened collaborative learning, and improved access to information. Nevertheless, several challenges were also identified, including academic integrity concerns, the quality of AI-generated responses, teachers’ readiness, and students’ digital literacy. This study contributes to the growing body of literature on the integration of generative artificial intelligence in Social Studies education by identifying existing research gaps and future research directions. Further studies are recommended to develop AI-based instructional models for Social Studies education and empirically examine their effectiveness in junior high school settings.